(untitled) (Journal of Hama University, 2021)
This study seeks to identify the role of psychological counselors in reducing school violence from the point of view of psychological counselors, and the study sample consisted of (100) psychological counselors in basic education schools in Lattakia Governorate in the Syrian Arab Republic, and the results showed that finding programs that protect Students from falling into the problem of school violence, and providing adequate opportunities for them to participate in activities that limit their violent behavior is one of the most important roles that a psychological counselor must play with students to reduce their violence in schools, after these options came within the first most important factor, which explains 54,903% From the study sample, the study also found that the fear of some families from the intervention of the psychological counselor in their private affairs, and the lack of conviction in the professional role of the psychological counselor are among the most important obstacles to the practice of psychological counselors for their role in reducing school violence.